Les fastes du parti 1885-1960 - Dhondt, Jan; Pierson, Marc-Antoine; De Weerdt, Denise; Collard, Leo (Bruxelles : PSB IEV, 1960)
Collectie Vrijzinnige Werkmansbibliotheek
Frans
Monografie
Keywords: POB; PSB; socialistische arbeidersbeweging